(untitled) (Proceedings of the Society of Antiquaries of Scotland, 1871)
This Roman carved stone has no more history known to me than that it was turned up by the plough on one of the farms on the Cumbernauld estate. The farmer’s name is Chalmers. I went to the spot where it was found, which is right over the Roman Wall.